2013
DOI: 10.1152/ajpcell.00221.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Rap1A signaling mediates cell surface translocation of microvascular smooth muscle α2C-adrenoceptors through the actin-binding protein filamin-2

Abstract: We recently demonstrated cAMP activation of Epac-Rap1A and RhoA-Rho-associated kinase (ROCK)-F-actin signaling in arteriolar-derived smooth muscle cells increases expression and cell surface translocation of functional ␣ 2C-adrenoceptors (␣ 2C-ARs) that mediate vasoconstriction in small blood vessels (arterioles). The Ras-related small GTPAse Rap1A increased expression of ␣ 2C-ARs and also increased translocation of perinuclear ␣ 2C-ARs to intracellular F-actin and to the plasma membrane. This study examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…Supporting this functional activation of RhoA by EPAC/Rap1A, inhibition of RhoA or downstream Rho-associated protein kinase, ROCK, arrested the EPAC/Rap1A-dependent F-actin enhancement (472). A followup study searched for the relation between ␣ 2c -adrenoreceptors translocation and F-actin uncovering a specific interaction between the COOH terminus of ␣ 2cadrenoreceptors and filamin-2, an actin cross-linker, using yeast-two hybrid screening (737). Indeed, forskolin, EPAC activation, and constitutively active Rap1A led to phosphorylation of filamin-2 at Ser2113 in a RhoA/ROCK-dependent manner, and consequently translocation of sequestered ␣ 2c -adrenoreceptors (737).…”
Section: Vascularmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting this functional activation of RhoA by EPAC/Rap1A, inhibition of RhoA or downstream Rho-associated protein kinase, ROCK, arrested the EPAC/Rap1A-dependent F-actin enhancement (472). A followup study searched for the relation between ␣ 2c -adrenoreceptors translocation and F-actin uncovering a specific interaction between the COOH terminus of ␣ 2cadrenoreceptors and filamin-2, an actin cross-linker, using yeast-two hybrid screening (737). Indeed, forskolin, EPAC activation, and constitutively active Rap1A led to phosphorylation of filamin-2 at Ser2113 in a RhoA/ROCK-dependent manner, and consequently translocation of sequestered ␣ 2c -adrenoreceptors (737).…”
Section: Vascularmentioning
confidence: 99%
“…A followup study searched for the relation between ␣ 2c -adrenoreceptors translocation and F-actin uncovering a specific interaction between the COOH terminus of ␣ 2cadrenoreceptors and filamin-2, an actin cross-linker, using yeast-two hybrid screening (737). Indeed, forskolin, EPAC activation, and constitutively active Rap1A led to phosphorylation of filamin-2 at Ser2113 in a RhoA/ROCK-dependent manner, and consequently translocation of sequestered ␣ 2c -adrenoreceptors (737). Therefore, EPAC/Rap1A appears to be implicated in vasoconstriction to initiate heat conservation after exposure to cold stimuli in the microvasculature.…”
Section: Vascularmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rather elegant and orchestrated series of events, α 2C -ARs then get in close proximity and associate with actin filaments, readying themselves for the trafficking process (Jeyaraj et al, 2012). This intimate association appears to be mediated by a direct interaction between α 2C -ARs and filamin-2, a cross-linker of actin filaments (Motawea et al, 2013). Indeed, further in silico protein-protein docking examinations confirmed that the interaction between α 2C -AR and F-actin occurs via the direct binding of α 2C -AR to filamin, the actin binding protein (Pawlowski et al, 2014).…”
Section: Rp and The Actin Cytoskeletonmentioning
confidence: 99%
“…The largest cluster had 41 structures, the 5 th best HADDOCK score (−91.2) and the 6 th best (lowest) electrostatic energy (−508.8) among all 10 clusters. However, the protein-protein interfaces among those structures did not involve any interactions between the C-terminal helix of ADRA2C and FLN2 between residues 1982 and 2183, as previously proven to occur by Motawea and coworkers [15]. Thus, among the ten most populated clusters, we searched for clusters that had receptor-filamin complexes having C-terminal helix of the receptor molecule involved in interactions with the filamin molecule.…”
Section: Resultsmentioning
confidence: 97%